Manajemen Pendidikan dan Tata Kelola Informasi: Analisis Peran Media Online dalam Bingkai Hukum dan Kebijakan Digital: Penelitian - Slamet Pamuji (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research discusses the role of online media corporations in influencing the direction of educational information through a digital legal and policy perspective. The development of information and communication technology has transformed the way people access and disseminate information, with online media becoming the dominant actor in shaping public opinion, including in the field of education. However, the dominance of digital media corporations poses serious challenges, especially related to the spread of inaccurate, misleading, or manipulative content. The main issue lies in corporate criminal liability, considering that the Indonesian legal system still faces ambiguity in distinguishing individual responsibility from corporate entities. This research uses a normative legal approach with a prescriptive nature, focusing on the analysis of laws and regulations, especially the Electronic Information and Transaction Law (ITE) and related criminal law provisions. Data was obtained through literature studies on primary, secondary, and tertiary legal materials. Qualitative analysis is carried out to interpret legal norms systematically and critically. The results of the study show that although the ITE Law has recognized corporations as legal subjects, its implementation still faces substantial obstacles. Progressive criminal law reform, clear law enforcement technical guidelines, and increased digital literacy of the community are needed.